Exploration of novel eco-friendly techniques to utilize bioactive compounds from household food waste: special reference to food applications - Siddique, Farzana; Ali, Zoha; Arshad, Muhammad; Mubeen, Kinza; Ghazala, Afsheen (Frontiers in Food Science and Technology, 2024)
The issue of household waste management is a pervasive global concern. Household waste, especially food waste, comprises a reservoir of compounds with potential economic value, among which bioactive compounds prominently feature. These bioactive compounds, derived from natural chemical substances inherent in waste from animal and protein sources, offer nutritional benefits. Extracted bioactive compounds find versatile applications in various domains including textiles, cosmetics, nutraceuticals, food additives, and the agriculture sector. The extraction of such compounds is achieved through a diversity of techniques, including conventional methods alongside non-conventional green approaches such as extraction methods using enzymes, microwaves, or supercritical fluids. However, there is an increasing need for green and sustainable approaches, leading to bioactive-rich extracts with low environmental impact. This review thoroughly summarizes the origins, kinds, and characteristics of bioactive chemicals found in food waste. It also addresses the most promising and innovative methodologies for the recovery of functional bioactive compounds from waste materials that have been published recently. New technologies can meaningfully manage materials from household food waste. These bioactive compounds are valuable for food industrial applications.